Junges Klima in Ottakring. - Tusch, Roland; Furchtlehner, Jürgen; Licka, Lilli (Forum Landschaftsplanung - AbsolventInnenverband, 2020)
Young climate in Ottakring. The consequences of global warming are particularly noticeable in high-density urban areas. Working with pupils on this issue and sensitizing them to act in a climate-friendly manner are the objectives of a current research project. On a meta-level it has been investigated how the involvement of young people in a research process influences their behavior and potentially makes them into change agents in their environment.

In Stadtteilen mit hoher Dichte sind die Folgen des Klimawandels besonders spürbar. Der klimagerechte Freiraum hat hier einen sehr hohen Stellenwert. Schülerinnen und Schüler für das Thema „Klimaerwärmung“ zu sensibilisieren und sie zu klimafreundlichem Handeln zu motivieren, sind Ziele des aktuellen Projekts.
Keywords: Klimawandel; Umweltbewusstsein; Umwelterziehung; Schüler; Forschungsprojekt